IDENTIFICATION AND MAPPING OF HOT SPOT AREAS SUSCEPTIBLE TO SOIL EROSION IN ERAK AL KARAK AREA USING GEOINFORMATICS - Mazahreh, Safa; Alkharabsheh, Mohammad; Bsoul, Majed; Hammor, Doaa Abu; Mahasneh, Lubna Al (International Journal of Research -GRANTHAALAYAH, 2018)
Jordan is a country dominated by arid climate and fragile ecological system, where 91% is classified as arid land with annual average rainfall rarely exceeds 200 mm/y. Therefore, land degradation, soil erosion and desertification are important areas of interest, where soil erosion is considered one of the major causes for land degradation in Jordan. The main objective of this study is to create an erosion hazard map and identify the areas susceptible to soil erosion in Erak Al karak watershed in southern part of Jordan. Soil erosion model RUSLE with the integration of GIS tools has been developed to estimate the annual soil loss. The estimated mean annual soil loss is (38.7 ton/ ha/year). The erosion map produced highlighted the hot spot areas susceptible to soil erosion. A relationship was obvious between terraces land use and soil loss, where 22% of the soil loss was reduced by applying soil conservation technique (terraces). According to this model, most of the hot spot areas are located in the rangeland 63% while the agricultural areas are responsible for 14% of the hot spot areas. The results emphasis the importance of urgent land use planning and conservation practices to reduce the impact of soil erosion.